Effect of the Protein Composition of Whole Nutrition Food for Special Medical Purposes on in Vitro Digestion Properties and Cell Calcium Transport Promotion - Weirong GUAN; Gengjie CUI; Shulin ZHENG; Na DONG; Yiming DING; Shengkai FANG; Hongyan LI; Jing WANG (Shipin gongye ke-ji)
In order to investigate the effects of in vitro digestive properties and pro-calcium transport of three whole nutrient foods for special medical purposes with distinct protein compositions (non-hydrolyzed protein B0, comprising approximately 55% whey protein and 45% casein, 100% non-hydrolyzed whey protein B1, and 100% moderately hydrolyzed whey protein B2). In vitro digestion study was conducted following the international INFOGEST method and the samples were subsequently analyzed for free α-amino acid content, degree of hydrolysis, peptide sequences, and amino acid composition. Furthermore, a Caco-2 monolayer cell model was established to explore the effects of three whole nutrient foods for special medical purposes on calcium transport both pre- and post-digestion. The results showed that when the digestion time was 240 min, the degrees of hydrolysis for non-hydrolyzed whey protein B1 and moderately hydrolyzed whey protein B2 were 50% and 45.5%, respectively, which were greater than that of non-hydrolyzed protein B0 (the degrees of hydrolysis was 36.5%), and the average peptide chain lengths for B1 and B2 were 5.06 and 4.52, respectively, both shorter than that of B0 (average peptide chain length of 5.45), suggesting that B1 and B2 exhibited greater in vitro digestibility. In addition, B2 contained a larger number of amino acids that could bind calcium, and it demonstrated superior calcium transport ability prior to digestion, with a transport amount of 32.20 µg over a transit time of 120 min, while after digestion, B1 exhibited enhanced calcium transport ability, with a transport amount of 35.70 µg at the same transit time. The bioavailability analysis of calcium revealed that the bioavailability of B0 and B2 before digestion, and B1 after digestion were 32.76%, 36.39%, and 40.60%, respectively, all exceeding that of CaCl2. These findings suggest that the three formulations above can effectively enhance calcium bioavailability and facilitate its absorption in the intestine. This study lays the groundwork for future investigations into whole nutrient foods for special medical purposes and provides valuable insights for the development of calcium supplement products.